Marine plastic: The solution is bigger than removal - García-Hermosa, M. Isabel; Woodall, Lucy C. (Frontiers in Sustainability, 2023)
Despite the increase in the documentation on, and interest in marine debris, there remains a gap between the analytic information and the policy recommendations developed by decision makers on how to reduce this pollutant. Our paper summarises some successful initiatives across policy, industry, infrastructure and education; and where they sit in the value chain of plastic products. We suggest that a multidisciplinary approach is required to address the marine plastic litter problem, which should emphasize 1) minimising plastic consumption (where possible) and waste leakage by 2) improving waste management (taking into consideration the informal sector) rather than clean-up activities. We then suggest some steps that once addressed would assist policy professionals with decisions to reduce marine plastic litter. The creation of a user-friendly tool that would facilitate transparency and democratisation of the decision-making process across stakeholders and the wider community and comprise information from points below. This list includes i) scoping the issue by agreeing on some metrics for quantifying plastic waste; ii) studying possible interventions from a proposed list taking into account the context specific nature of interventions/solutions; iii) identifying the main influential factors specific to the situation/region; iv) identifying the risks associated to the selected interventions and the influence/consequences of these interventions on the most influential factors; v) objectively ranking/ prioritising solutions using the previous points (metrics, targets, risks, factors) based on the regional, national, and or international context.